Evolution of the Oil Shale Permeability under Real-Time High-Temperature Triaxial Stress in the Jimusar Area, Xinjiang - Lusheng Yang; Peng Li (Geofluids)
This paper adopts a real-time high-temperature triaxial seepage test system to study the permeability evolution of oil shale in the Jimusar area, Xinjiang, with the temperature, pore pressure, and volumetric stress. The results indicate that (1) the variation process of the oil shale permeability with the temperature can be divided into three stages: slow growth stage from 20 to 350°C, rapid growth stage from 350 to 500°C with a threshold temperature of 400°C, and growth deceleration stage from 500 to 600°C. (2) With increasing pore pressure, the permeability gradually decreases. Under a volumetric stress of 17 MPa, the permeability decreases the most rapidly from 1 to 2 MPa, and under a volumetric stress of 34 MPa, the permeability decreases the fastest from 1 to 3 MPa. (3) The oil shale permeability decreases with increasing volumetric stress. At room temperature, the decrease magnitude of the permeability is small and increases with increasing temperature. The results can provide a theoretical reference for the analysis of the seepage process of thermal fluids and pyrolysis oil and gas in oil shale.